Shortening the Tenure Clock: the Impact of Strengthened U.K. Job Security Legislation - Ioana Marinescu (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2007)
This paper uses the fact that firing costs are tenure dependent to analyze their effect on turnover and productivity. I exploit a 1999 British reform that lowered from two to one year the tenure necessary for a worker to be able to sue their employer for unfair dismissal. Empirical results show a roughly 30% decrease in the firing hazard for workers with zero to two years of tenure relative to workers with higher tenure. Training increased after the reform, unemployment duration decreased, and wages were unaffected. Theory suggests that the decrease in firing for low tenure workers is mainly due to a sizeable increase in the quality of recruitment.
Keywords: J24; J41; J63; J64; J65; J83; 330; Firing Costs; Separation Hazard Rate; Learning; Job Tenure